Development Of Dried Black Grass Jelly (Mesona Chinensis) Containing Different Tapioca And Sago Starch Ratio - Oon, Li Juen
Black grass jelly is a herbal dessert made from dried leaves extracts of Mesona chinensis plant. Commercial black grass jelly exhibits a short shelf life when stored at room temperature due to the usage of tapioca starch which results in a higher syneresis rate and unstable texture. Hence, the objective of this research is to develop dried black grass jelly with different tapioca and sago starch ratio for increasing the shelf life of the black grass jelly. The black grass jelly was formulated with different sago and tapioca starch ratio (0:100, 25:75, 50:50, 75:25, 100:0), thereafter dried at different drying time (0, 3, 6, 9, 12, 24, 30 hr) and rehydrated at 90 ℃ for 15 min. The development of dried black grass jelly containing different tapioca and sago starch ratio was successful. The effects of different sago and tapioca starch ratio and drying time on the physical properties of black grass jelly were determined. Hence, analyses on the moisture content, colour, texture, syneresis, drying kinetics (moisture content against drying time) and rehydration capacity were conducted. The increase in sago starch ratio significantly decreased (p<0.05) the moisture content of fresh black grass jelly consisting of both starches. The values of all the colour parameters and textural parameters except springiness, of the fresh black grass jelly increased significantly (p<0.05) in comparison with control sample when the sago starch ratio was increased to more than 75%. Different sago and tapioca starch ratio did not significantly affect (p>0.05) the syneresis of black grass jelly after storage for 24 hr, however the syneresis of fresh black grass jelly significantly (p<0.05) increased with the increase in storage time. A non-linear relationship was observed on the drying curve of black grass jelly.